The influence of wearing masks and gloves due to COVID-19 pandemic on skin problems and skin care in students of Medical University in Lublin - Aleksandra Jaremek; Wiktoria Chodun; Justyna Piechnik; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2020)
Introduction. Our everyday life has changed drastically in these few months. The arrival of the new 2019-nCoV virus in December 2019 and its rapid spread from the city of Wuhan, China, has highlighted the increase in personal protective equipment (PPE). The aim of the study was to to learn about   the influence of wearing masks and gloves due to COVID-19 pandemic on skin problems and skin care in students of Medical University in Lublin. Material and methods. In October 2020, we conducted a survey with use of a questionnaire. Results. A total of 59 persons completed the questionnaire. Only one person reported not wearing the mask as recommended. For 54% of participants, wearing a mask had an impact on the occurrence of skin problems, such as acne. A similar number of respondents answered positively to the question about the influence of masks on their makeup. These people used to wear much less makeup. Most of them only paint the eyes because the material is covering the mouth. More than half of the respondents do not wear gloves, they wash or disinfect hands. In 61% of respondents, there was no problems with hand  skin or nails, such as brittleness, mycosis, discoloration, allergic dermatitis or contact dermatitis. The vast majority cared more about moisturizing the skin of the hands. Conclusion. Wearing masks by students of Medical University of Lublin increases skin problems like acne and reduces the amount of makeup applied. Due to wearing gloves students focus more on moisturizing the skin.